A copper-silver composite catalyst and its preparation method and application

By using the core-shell structure and tandem reaction mechanism of the copper-silver composite catalyst, the problem of low selectivity of polycarbon products in electrocatalytic reduction of carbon dioxide is solved, and efficient C2+ product selectivity and catalyst stability are achieved.

CN115404499BActive Publication Date: 2025-04-22ZHEJIANG UNIV

Patent Information

Application Number
CN202210954604.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-10
Publication Date
2025-04-22
Estimated Expiration
2042-08-10

AI Technical Summary

Technical Problem

In the electrocatalytic reduction reaction of carbon dioxide, the selectivity of producing polycarbon products is not high, the catalyst synthesis process is complicated, and the selective conversion of existing catalysts to polycarbon products has problems with high overpotential, low reaction rate and low selectivity.

Method used

The copper-silver composite catalyst is used, which uses a core-shell structure with a copper-silver mixture as the core and copper as the shell. By constructing a tandem reaction from the Ag active site to the Cu active site, the copper-silver synergistic effect induces the reaction to develop into the multi-carbon product path, thereby improving the selectivity of C2+ products.

Benefits of technology

When catalytic reduction of carbon dioxide, the selectivity of C2+ products is achieved by more than 80%, which improves the current density and stability of the catalyst, enhances the selectivity of multi-carbon products, especially the high selectivity of ethanol.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115404499B_ABST
    Figure CN115404499B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrocatalytic reduction technology, and specifically discloses a copper-silver composite catalyst and its preparation method and application. The copper-silver composite catalyst is a core-shell structure with a copper-silver mixture as a core and copper as a shell, wherein the copper of the copper-silver mixture in the core is in a metallic state or a monovalent state, and the copper in the shell is in an oxidized state. The preparation process is to immerse an organic binuclear copper precursor and silver nanoparticles in a solvent, dry them, and then roast them. The present invention constructs a tandem reaction from the Ag active site to the Cu active site, which can effectively exert the good hydrogen evolution reaction inhibition effect of the silver-based catalyst and the superior C-C coupling performance of the copper-based catalyst. When applied to the carbon dioxide electroreduction system, it can induce the reaction to develop towards a multi-carbon product path through the copper-silver synergistic effect, and finally achieve a higher C 2+ Product selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrocatalytic reduction, and in particular to a copper-silver composite catalyst and a preparation method and application thereof. Background Art

[0002] With the continuous growth of the global population and the development of industry, the demand for fossil fuels is increasing day by day. The large amount of carbon dioxide emitted by the use of fossil fuels has an adverse impact on the global environment, and the situation of global climate change is becoming more and more severe. High concentrations of carbon dioxide in the atmosphere will lead to a series of environmental problems, such as global warming, desertification, ocean acidification, and species extinction. How to reduce carbon emissions is an issue that needs to be solved by all countries in the world. Since 2003, China has been committed to promoting low-carbon, environmentally friendly, energy-saving and emission-reducing life, and controlling greenhouse gas emissions, mainly carbon dioxide. However, based on the expected economic growth rate, total energy demand will continue to grow for a certain period of time.

[0003] Carbon capture, utilization and storage (CCUS) is an internationally recognized technology that can achieve direct emission reduction and resource utilization of fossil energy in CO2 emission reduction technology. Structurally, the carbon dioxide molecule is linear and centrosymmetric, which gives it special stability, inherent chemical inertia, low electron affinity and a large energy gap (13.7 eV). Therefore, the conversion of carbon dioxide is an endothermic process that requires a large amount of energy input. At present, there are various ways to convert carbon dioxide into carbon-based chemicals and fuels, including chemical reforming, biochemical, photochemical, thermochemical and electrochemical reduction.

[0004] Among these technologies, electrochemical carbon dioxide reduction technology (CO2RR) driven by clean and renewable energy such as solar energy and wind energy provides broad prospects for large-scale industrial applications and has great application potential because it operates under relatively mild reaction conditions such as ambient temperature and atmospheric pressure. Its technical advantages include mild reaction conditions, controllable application voltage and reaction temperature, recyclable supporting electrolytes, non-contaminated input energy, and easy expansion of applications. However, researchers in the field of carbon dioxide electrocatalytic reduction still face key issues such as large overpotential, slow electron transfer kinetics, unsatisfactory selectivity for specific products, and low energy efficiency due to accompanying solvent decomposition reactions. How to efficiently utilize carbon dioxide and convert it into organic compounds such as CO and methane, formic acid, methanol, ethylene, ethanol and propanol that are easy to store and transport is a global problem and an emerging research hotspot.

[0005] The CO2RR process is a complex multi-step reaction process. Depending on the conditions such as the number of electrons transferred in the reaction, the products of the cathode-catalyzed CO2 reduction may be a variety of different substances. Since the reaction potential of the hydrogen evolution reaction (HER) is usually equivalent to the CO2 equilibrium potential in theory, the hydrogen evolution reaction often becomes its competing reaction. The electrochemical reduction of CO2 at the cathode is divided into multiple steps. In the actual reaction process, these steps are often affected by internal factors such as electrode materials, electrolyte composition, temperature, and external factors such as the actual potential applied to the electrode surface. The products of CO2RR are a variety of carbon compounds, which are divided into carbon one (C1) products (CO, CH4, HCOO) according to the number of carbon elements in the products. - and CH3OH) and multi-carbon products (C 2+ Compared with C1 products, some multi-carbon products (C2H4, C2H5OH, CH3COO - , n-C3H7OH, etc.) have a high volume energy density and can be directly used as the basis for synthesizing long-chain hydrocarbon fuels and oxygenates.

[0006] However, carbon dioxide to C 2+ The selective conversion of products is characterized by high overpotential, low reaction rate and low selectivity, and the process is extremely sensitive to catalyst structure and electrolyte. The formation of CC bonds under electrocatalytic reduction conditions competes with the formation of CH and CO bonds, making the production of multi-carbon products very difficult.

[0007] CN114000177A discloses a Ag@Cu2O core-shell structure nanosphere catalyst and its preparation method and application, which comprises adding copper salt and reducing agent to the silver nanosphere dispersion, centrifuging, washing and drying to obtain the Ag@Cu2O core-shell structure nanosphere electrocatalyst. The invention provides a synergistic series catalysis between copper and silver catalysts through the core-shell structure. The copper shell layer coated on the surface of the silver nanosphere exposes more copper reaction active sites, promotes CC coupling, and improves its selectivity for multi-carbon products. However, the main product is ethylene, the hydrogen evolution reaction is serious, and the intermediate product is not fully utilized. * CO is easily desorbed to form product carbon monoxide. Summary of the invention

[0008] The present invention aims to solve the problem of low selectivity of carbon dioxide electrocatalytic reduction reaction to generate multi-carbon products in the prior art, and the complex and cumbersome catalyst synthesis process. A copper-silver composite catalyst is provided, which constructs a series reaction from Ag active sites to Cu active sites, and induces the reaction to develop towards a multi-carbon product path through the synergistic effect of copper and silver, and finally achieves a higher C 2+ Product selectivity, C at -1.0 V (vs. RHE) in the catalytic reduction of CO2 2+The product selectivity can reach over 80%.

[0009] To achieve the above object, the technical solution adopted by the present invention is:

[0010] A copper-silver composite catalyst has a core-shell structure with a copper-silver mixture as a core and copper as a shell, wherein the copper of the copper-silver mixture in the core is in a metallic state or a monovalent state, and the copper in the shell is in an oxidized state.

[0011] The content of copper in the copper-silver composite catalyst is 1-50 wt %; preferably, the content of copper is 3-40 wt %, and more preferably 5-30 wt %.

[0012] In the present invention, a series reaction is constructed from the Ag active site to the Cu active site, which can effectively exert the good hydrogen evolution reaction inhibition effect of the silver-based catalyst and the superior CC coupling performance of the copper-based catalyst. During electrochemical reduction, the copper in the oxidation state of the shell will be converted into a metallic state in situ, called OD-Cu (oxide-derived copper), which has a lower starting potential and can improve the selectivity for specific products (such as alcohols). After electroreduction, Cu and Ag are both in a metallic state. The principle of the series reaction means that CO2 is preferentially adsorbed on Ag, reduced to CO, and then transferred to Cu for CC coupling until C2 products such as ethanol and ethylene are generated. Since the energy barrier for CC coupling to generate ethanol on the core-shell catalyst of the present invention is low, the ethanol selectivity is high during catalysis. The catalyst in the present invention is a solid solution composed of Cu and Ag, and there are more copper-silver interfaces, which can make more full use of the intermediate products. * CO and undergo CC coupling to promote the formation of subsequent multi-carbon products (especially ethanol products).

[0013] The core size of the copper-silver mixture is 10-500nm, and the shell thickness of the copper is 10-50nm. The core size is too large and it is not easy to form a core-shell structure.

[0014] The invention provides a method for preparing the copper-silver composite catalyst, which comprises impregnating an organic binuclear copper precursor and silver nanoparticles in a solvent, drying the mixture and then calcining the mixture to obtain the copper-silver composite catalyst.

[0015] Since the organic binuclear copper precursor and the Ag nanoparticles have functional groups such as hydroxyl groups on their surfaces, they can self-assemble into AgCu complexes through van der Waals forces or hydrogen bonds. Then, at medium and high temperatures, the incompatibility between Cu and Ag is utilized to cause the Ag nanoparticles to agglomerate in the core, while Cu gradually migrates to the surface.

[0016] The impregnation time is 1-24h; the roasting temperature is 250-400℃, and the roasting time is not less than 10h.

[0017] The preferred calcination time is 10-24 hours to completely decompose the added organic binuclear copper precursor;

[0018] The mass ratio of the organic binuclear copper precursor to the silver nanoparticles is (1-50):100; when the Cu content is low, a structure in which a small amount of Cu is dispersed in the Ag nanoparticles is formed; when the Cu content is high, Cu will gather outside the Ag nanoparticles to form a Cu and Ag phase separation structure. However, the composite catalyst prepared according to the method generally has a good catalytic effect and has excellent C 2+ Selective.

[0019] The solvent includes any one of methanol, ethyl acetate, ethanol and water.

[0020] The impregnation process usually selects a solid:liquid volume ratio of 1:1-1:10; if there is too much liquid, the subsequent wastewater treatment cost will increase.

[0021] The silver nanoparticle preparation process comprises the steps of: adding a silver precursor and ascorbic acid to a polyvinyl pyrrolidone solution in sequence, obtaining a silver nanoparticle crude product by chemical reduction reaction, and obtaining the silver nanoparticle by centrifugation, washing and drying.

[0022] The molar ratio of polyvinyl pyrrolidone, silver precursor salt and ascorbic acid is 1:(10-20):(0.64-1.28).

[0023] In the process of preparing silver nanoparticles, the silver precursor includes one or more of silver nitrate, silver citrate, silver sulfate, silver bromide, and silver chloride; the particle size of the silver nanoparticles is 1-500nm; and the chemical reduction reaction time is 1-24h.

[0024] Preferably, the particle size of the silver nanoparticles is 10-50 nm, and the chemical reduction reaction time is 2 hours.

[0025] The solvent of the polyvinyl pyrrolidone solution in the preparation process includes water and ethanol. The silver precursor and ascorbic acid can be dissolved in advance and then added in sequence, or can be added directly.

[0026] The silver nanoparticles are washed using one or more solvents such as ethanol, ethyl acetate, methanol, and water.

[0027] The preparation process of the organic binuclear copper precursor comprises the following steps:

[0028] The copper precursor solution, bipyridine solution and organic acid solution are mixed, and during the stirring process, a precipitate is generated due to the surface self-assembly effect, and the organic binuclear copper precursor is obtained through centrifugation, washing and drying.

[0029] The molar ratio of the copper salt, bipyridine and organic acid is (1-5):(1-5):1.

[0030] The copper precursor is an inorganic copper salt, including one or more of copper nitrate, copper acetate, copper chloride, copper phthalocyanine, and copper acetylacetonate;

[0031] The bipyridine includes one or more of 2,2'-bipyridine, 4,4'-bipyridine, and α,α,α-terpyridine;

[0032] The organic acid includes one or more of oxalic acid, acetic acid, propionic acid, citric acid, and tartaric acid;

[0033] In order to mix evenly, each raw material is first prepared into a solution, and then mixed for better effect. The solvent is polar solvent such as water and methanol, and the reaction time is 1-24h.

[0034] The organic binuclear copper precursor is washed by one or more solvents such as water, methanol, ethanol and ethyl acetate.

[0035] The present invention provides application of the copper-silver composite catalyst in an electrocatalytic carbon dioxide reduction reaction.

[0036] The copper-silver composite catalyst is coated on a conductive material, such as carbon paper, carbon cloth, glassy carbon electrode, etc., or a combination of two or more thereof. The reaction potential is -0.5V vs. RHE to -1.2V vs. RHE at room temperature and pressure, and the electrolyte is a 0.1-3M neutral or alkaline electrolyte, including but not limited to potassium hydroxide, potassium bicarbonate, etc., which can promote the reduction of carbon dioxide to products such as carbon monoxide, formic acid, ethylene, and ethanol under electrocatalytic conditions.

[0037] The copper-silver composite catalyst of the present invention has a synergistic effect on the copper-silver reaction, which induces the reaction to develop towards a multi-carbon product path, and finally reaches a higher C 2+ Product selectivity.

[0038] Compared with the prior art, the present invention has the following beneficial effects:

[0039] The copper-silver composite catalyst of the present invention has a core of a copper-silver mixture and a shell of copper oxide, and constructs a series reaction from the Ag active site to the Cu active site, which can effectively exert the good hydrogen evolution reaction inhibition effect of the silver-based catalyst and the superior CC coupling performance of the copper-based catalyst. The copper-silver synergistic effect induces the reaction to develop towards a multi-carbon product path, and finally achieves a higher C 2+ Product selectivity. Compared with the existing technology, it has the advantages of high current density, strong stability, high selectivity for multi-carbon products and high selectivity for the main liquid phase product ethanol. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a complete TEM image of the copper-silver composite catalyst prepared in Example 1.

[0041] Figure 2 This is a TEM image of the core part of the copper-silver composite catalyst prepared in Example 1.

[0042] Figure 3 This is a TEM image of the shell portion of the copper-silver composite catalyst prepared in Example 1.

[0043] Figure 4 This is the argon etching XPS graph of the copper-silver composite catalyst prepared in Example 1.

[0044] Figure 5 This is the Faraday efficiency diagram of the total product of the electrochemical reaction of the copper-silver composite catalyst prepared in Example 1 of Application Example 1.

[0045] Figure 6 When the copper-silver composite catalyst prepared in Examples 1-4 and Comparative Examples 1-3 in Application Example 1 is used, C 2+ Product Faradaic efficiency versus voltage.

[0046] Figure 7 This is the electrochemical stability test of Example 1 in Application Example 2 at -0.9 V vs. RHE. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiment. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Those skilled in the art can make modifications or equivalent substitutions based on the understanding of the technical scheme of the present invention without departing from the spirit and scope of the technical scheme of the present invention, and all should be included in the protection scope of the present invention.

[0048] The raw materials used in the following specific embodiments are all purchased from the market.

[0049] Example 1

[0050] Step 1, weigh 3g of polyvinyl pyrrolidone and dissolve it in 30mL of ultrapure water, 150mg of silver citrate and dissolve it in 30mL of ultrapure water, and 30mg of ascorbic acid and dissolve it in 30mL of ultrapure water, and ultrasonicate each for 30min until it is completely dissolved. Slowly add the silver citrate solution and the ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h, and then centrifuge and separate, wash alternately with ethanol and ethyl acetate three times, and dry in a vacuum drying oven overnight to obtain silver nanoparticles with a particle size of 50nm.

[0051] Step 2: weigh 544 mg of copper chloride and dissolve it in 40 mL of ultrapure water, 496 mg of 2,2'-bipyridine and dissolve it in 20 mL of methanol, and 200 mg of oxalic acid and dissolve it in 20 mL of ultrapure water, and ultrasonicate each for 30 min until it is completely dissolved. Slowly drop the 2,2'-bipyridine methanol solution and the oxalic acid solution into the copper chloride solution under vigorous stirring, continue stirring for 1 hour, and then centrifuge and wash it alternately with water and methanol three times, and dry it in a vacuum drying oven overnight to obtain an organic binuclear copper precursor.

[0052] Step 3, ultrasonically disperse the organic binuclear copper precursor and silver nanoparticles in a small amount of methanol solution at a mass ratio of 25:100, stir and evaporate to dryness, and then transfer to a muffle furnace, set the temperature to rise from 50°C at a rate of 2°C / min to 250°C and maintain for 10 hours.

[0053] Step 4: After the catalyst obtained in the above step is naturally cooled, the catalyst is taken out into a mortar and ground into powder to obtain the catalyst of Example 1.

[0054] The prepared catalyst was subjected to microscopic morphology observation, such as TEM Figure 1-3 As shown in the figure, the sample is a core-shell structure, and judging from the measured lattice fringe spacing, Figure 2 The middle core is visible as a mixture of Cu2O and Ag, with a size of about 100nm; Figure 3 The middle shell is CuO, and the shell thickness is 10-20nm.

[0055] The copper content of the obtained copper-silver composite catalyst was 5%. The molecular structure and atomic valence state of the obtained catalyst were analyzed. The argon etching XPS results showed that Figure 4 The copper in the outer shell is Cu(II), and after argon etching of 10nm-20nm, the copper in the inner core is Cu(I).

[0056] Example 2

[0057] This embodiment provides a method for preparing a carbon dioxide electrocatalytic reduction catalyst, comprising the following steps:

[0058] Step 1, weigh 3g of polyvinyl pyrrolidone and dissolve it in 30mL of ultrapure water, 150mg of silver citrate and dissolve it in 30mL of ultrapure water, and 30mg of ascorbic acid and dissolve it in 30mL of ultrapure water, and ultrasonicate each for 30min until it is completely dissolved. Slowly add the silver citrate solution and the ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h, and then centrifuge and separate, wash alternately with ethanol and ethyl acetate three times, and dry in a vacuum drying oven overnight to obtain silver nanoparticles with a particle size of 50nm.

[0059] Step 2: weigh 544 mg of copper chloride and dissolve it in 40 mL of ultrapure water, 496 mg of 2,2'-bipyridine and dissolve it in 20 mL of methanol, and 200 mg of oxalic acid and dissolve it in 20 mL of ultrapure water, and ultrasonicate each for 30 min until it is completely dissolved. Slowly drop the 2,2'-bipyridine methanol solution and the oxalic acid solution into the copper chloride solution under vigorous stirring, continue stirring for 1 hour, and then centrifuge and wash it alternately with water and methanol three times, and dry it in a vacuum drying oven overnight to obtain an organic binuclear copper precursor.

[0060] Step 3, ultrasonically disperse the organic binuclear copper precursor and silver nanoparticles in a small amount of methanol solution at a mass ratio of 50:100, stir and evaporate to dryness, and then transfer to a muffle furnace, set the temperature to rise from 50°C at a rate of 2°C / min to 250°C and maintain for 10 hours.

[0061] After the catalyst obtained in the above steps is naturally cooled, the catalyst is taken out of a mortar and ground into powder to obtain the catalyst of Example 2, which has a copper content of 10%.

[0062] Example 3

[0063] This embodiment provides a method for preparing a carbon dioxide electrocatalytic reduction catalyst, comprising the following steps:

[0064] Step 1, weigh 3g of polyvinyl pyrrolidone and dissolve it in 30mL of ultrapure water, 150mg of silver citrate and dissolve it in 30mL of ultrapure water, and 30mg of ascorbic acid and dissolve it in 30mL of ultrapure water, and ultrasonicate each for 30min until it is completely dissolved. Slowly add the silver citrate solution and the ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h, and then centrifuge and separate, wash alternately with ethanol and ethyl acetate three times, and dry in a vacuum drying oven overnight to obtain silver nanoparticles with a particle size of 50nm.

[0065] Step 2: weigh 544 mg of copper chloride and dissolve it in 40 mL of ultrapure water, 496 mg of 2,2'-bipyridine and dissolve it in 20 mL of methanol, and 200 mg of oxalic acid and dissolve it in 20 mL of ultrapure water, and ultrasonicate each for 30 min until it is completely dissolved. Slowly drop the 2,2'-bipyridine methanol solution and the oxalic acid solution into the copper chloride solution under vigorous stirring, continue stirring for 1 hour, and then centrifuge and wash it alternately with water and methanol three times, and dry it in a vacuum drying oven overnight to obtain an organic binuclear copper precursor.

[0066] Step 3, ultrasonically disperse the organic binuclear copper precursor and silver nanoparticles in a small amount of methanol solution at a mass ratio of 150:100, stir and evaporate to dryness, and then transfer to a muffle furnace, set the temperature to rise from 50°C at a rate of 2°C / min to 250°C and maintain for 10 hours.

[0067] After the catalyst obtained in the above steps is naturally cooled, the catalyst is taken out of a mortar and ground into powder to obtain the catalyst of Example 3, which has a copper content of 30%.

[0068] Example 4

[0069] This embodiment provides a method for preparing a carbon dioxide electrocatalytic reduction catalyst, comprising the following steps:

[0070] Step 1, weigh 3g of polyvinyl pyrrolidone and dissolve it in 30mL of ultrapure water, 150mg of silver citrate and dissolve it in 30mL of ultrapure water, and 30mg of ascorbic acid and dissolve it in 30mL of ultrapure water, and ultrasonicate each for 30min until it is completely dissolved. Slowly add the silver citrate solution and the ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h, and then centrifuge and separate, wash alternately with ethanol and ethyl acetate three times, and dry in a vacuum drying oven overnight to obtain silver nanoparticles with a particle size of 50nm.

[0071] Step 2: weigh 544 mg of copper chloride and dissolve it in 40 mL of ultrapure water, 496 mg of 2,2'-bipyridine and dissolve it in 20 mL of methanol, and 200 mg of oxalic acid and dissolve it in 20 mL of ultrapure water, and ultrasonicate each for 30 min until it is completely dissolved. Slowly drop the 2,2'-bipyridine methanol solution and the oxalic acid solution into the copper chloride solution under vigorous stirring, continue stirring for 1 hour, and then centrifuge and wash it alternately with water and methanol three times, and dry it in a vacuum drying oven overnight to obtain an organic binuclear copper precursor.

[0072] Step 3, ultrasonically disperse the organic binuclear copper precursor and silver nanoparticles in a small amount of methanol solution at a mass ratio of 10:100, stir and evaporate to dryness, and then transfer to a muffle furnace, set the temperature to rise from 50°C at a rate of 2°C / min to 250°C and maintain for 10 hours.

[0073] After the catalyst obtained in the above steps is naturally cooled, the catalyst is taken out of a mortar and ground into powder to obtain the catalyst of Example 4, which has a copper content of 2%.

[0074] Comparative Example 1

[0075] Weigh 2g of polyvinyl pyrrolidone and 454mg of copper acetate and dissolve them in 50mL of ethanol, mix and stir in a 60°C water bath for 60min. Weigh 1.76g of ascorbic acid and dissolve it in 30mL of ethanol, slowly dropwise add it to the original solution and continue stirring for 10min. After centrifugation, wash it three times alternately with water and ethanol, dry it in a vacuum drying oven overnight, and grind it to obtain the catalyst of Comparative Example 1.

[0076] Comparative Example 2

[0077] Weigh 3g of polyvinyl pyrrolidone and dissolve it in 30mL of ultrapure water, 150mg of silver citrate and dissolve it in 30mL of ultrapure water, and 30mg of ascorbic acid and dissolve it in 30mL of ultrapure water, and each is ultrasonicated for 30min until completely dissolved. Slowly add silver citrate solution and ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h and then centrifuge. Wash it alternately with water and ethanol three times, dry it in a vacuum drying oven overnight, and grind it to obtain the catalyst of Comparative Example 2.

[0078] Comparative Example 3

[0079] Step 1, weigh 2g polyvinyl pyrrolidone and 454mg copper acetate, dissolve in 50mL ethanol, mix and stir in a 60°C water bath for 60min. Then weigh 1.76g ascorbic acid, dissolve in 30mL ethanol, slowly dropwise add to the original solution and continue stirring for 10min. After centrifugation, wash three times with water and ethanol alternately, dry in a vacuum drying oven overnight, and grind to obtain the copper nanoparticles.

[0080] Step 2, weigh 3g polyvinyl pyrrolidone and dissolve it in 30mL ultrapure water, 150mg silver citrate and dissolve it in 30mL ultrapure water, 30mg ascorbic acid and dissolve it in 30mL ultrapure water, each ultrasonic for 30min until completely dissolved. Slowly add silver citrate solution and ascorbic acid solution to the polyvinyl pyrrolidone solution while stirring, continue stirring for 1h and then centrifuge. Wash it alternately with water and ethanol three times, dry it in a vacuum drying oven overnight, and grind it to obtain the silver nanoparticle catalyst.

[0081] Step 3, the copper nanoparticles and silver nanoparticles obtained in the above step are uniformly mixed in 1 mL of methanol solution at a mass ratio of 5:100, stirred and evaporated to dryness, and then transferred to a muffle furnace, set to start from 50°C and increase the temperature at a rate of 2°C / min to 250°C and maintain for 10 hours.

[0082] After the catalyst obtained in the above steps is naturally cooled, the catalyst is taken out of a mortar and ground into powder to obtain the catalyst of Comparative Example 3.

[0083] Application Example 1

[0084] The electrochemical reduction test of the electrochemical reduction catalysts prepared in the above Examples 1-4 and Comparative Examples 1-3 was performed. The above catalysts were added with water and ethanol and ultrasonicated for 30 minutes. Then 5% Nafion solution was added, ultrasonicated for 30 minutes in an ice water bath, stirred overnight, and drop-coated on a carbon paper electrode and dried overnight. The flow electrolytic cell was assembled, and 3M potassium hydroxide electrolyte was configured to perform the electrochemical activity test. Figure 5 The current density and total product Faraday efficiency distribution diagram of Example 1 at different potentials. 2+The relationship between the product Faraday efficiency and voltage is as follows Figure 6 As shown, it can be seen that at a potential of -1.0 V vs. RHE, the C 2+ The product has the highest Faraday efficiency, which can reach 80.23%.

[0085] Application Example 2

[0086] The catalyst prepared in Example 1 was tested for stability in an electrochemical reduction of carbon dioxide experiment. Take 10 mg of the catalyst obtained in Example 1, add water and ethanol, and ultrasonicate for 30 minutes. Then add 5% Nafion solution, ultrasonicate in an ice-water bath for 30 minutes, stir overnight, drop-coat on a carbon paper electrode, and dry naturally overnight. Assemble a flow electrolytic cell, configure 3M potassium hydroxide electrolyte, and perform an electrochemical activity test. A constant potential test was performed at a potential of -0.9 V vs. RHE, and gas samples were detected by gas chromatography every 1-2 hours. Liquid samples were collected and product detection was performed by liquid nuclear magnetic resonance. The current and ethanol Faraday efficiency results at a potential of -0.9 V vs. RHE are shown below. Figure 7 It can be seen that the copper-silver composite catalyst prepared in Example 1 has strong reaction stability, which can reach 60 hours, and the Faraday efficiency of ethanol is maintained at 50%.

[0087] up and down.

Claims

1. A copper-silver composite catalyst, characterized in that: The copper-silver composite catalyst is a core-shell structure with a copper-silver mixture as a core and copper as a shell, wherein the copper of the copper-silver mixture in the core is in a metallic state or a monovalent state, and the copper in the shell is in an oxidized state; The content of copper element in the copper-silver composite catalyst is 1-50wt%, the core size of the copper-silver mixture is 10-500nm, and the shell thickness of copper is 10-50nm.

2. The method for preparing the copper-silver composite catalyst according to claim 1, characterized in that: The organic binuclear copper precursor and silver nanoparticles are impregnated in a solvent, dried and then calcined to obtain the copper-silver composite catalyst; The mass ratio of the organic binuclear copper precursor to the silver nanoparticles is 1-50:100; The preparation of the organic binuclear copper precursor comprises: mixing a copper precursor solution, a bipyridine solution and an organic acid solution, stirring to react to generate a product, and centrifuging, washing and drying to obtain the organic binuclear copper precursor.

3. The method for preparing the copper-silver composite catalyst according to claim 2, characterized in that: The impregnation time is 1-24 hours; and / or the roasting temperature is 250-400° C., and the roasting time is not less than 10 hours.

4. The method for preparing the copper-silver composite catalyst according to claim 2, characterized in that: The solvent includes any one of methanol, ethyl acetate, ethanol and water.

5. The method for preparing the copper-silver composite catalyst according to claim 2, characterized in that: The preparation of the silver nanoparticles comprises: sequentially adding a silver precursor and ascorbic acid into a polyvinyl pyrrolidone solution, chemically reducing the solution to obtain a crude product of the silver nanoparticles, and centrifuging, washing and drying the solution to obtain the silver nanoparticles.

6. The method for preparing the copper-silver composite catalyst according to claim 5, characterized in that: The silver precursor includes one or more of silver nitrate, silver citrate, silver sulfate, silver bromide, and silver chloride; And / or, the silver nanoparticles have a particle size of 1-500 nm; And / or, the chemical reduction reaction time is 1-24h.

7. The method for preparing the copper-silver composite catalyst according to claim 2, characterized in that: The copper precursor is an inorganic copper salt, including one or more of copper nitrate, copper acetate, copper chloride, copper phthalocyanine, and copper acetylacetonate; The bipyridine includes one or more of 2,2'-bipyridine, 4,4'-bipyridine, α,α,α-terpyridine; the organic acid includes one or more of oxalic acid, acetic acid, propionic acid, citric acid, and tartaric acid; And / or, the reaction time is 1-24h.

8. Use of the copper-silver composite catalyst according to claim 1 in an electrocatalytic carbon dioxide reduction reaction.

Citation Information

Patent Citations

  • Cu2O@Cu / AgBr composite light catalyst and preparation method thereof

    CN105879887A

  • Core-shell structured Ag@Cu nanoparticle conductive ink, and preparation method and use thereof

    CN109852146A

Cited By

  • M (MYO) / COFX catalyst and M (MYO) / COFX electrode as well as preparation method and application of M (MYO) / COFX electrode

    CN122189752A